A Cognitive-Orthographic Analysis of Spelling Errors in Descriptive Writing among Indonesian EFL Students - Erika Salsabila; Sudar; Ismawati Ike Nugraeni (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates the types of spelling errors found in descriptive texts written by Indonesian EFL learners and examines the linguistic factors contributing to these errors. Using a descriptive qualitative design with an error analysis approach, the study analyzed 39 spelling errors produced by 24 eleventh-grade students at SMA Muhammadiyah Kutoarjo. The errors were classified based on the Surface Strategy Taxonomy, including omission, substitution, addition, and transposition. The findings revealed that omission was the most frequent error type (38.46%), followed by substitution (30.77%), addition (20.51%), and transposition (10.26%). The analysis indicates that students’ spelling difficulties are strongly influenced by the inconsistency of English orthography and interference from Indonesian phonological patterns. The findings also suggest that learners tend to rely on phonetic spelling strategies when dealing with unfamiliar English words. Although limited by a small sample size and a single educational context, this study provides valuable insights into the orthographic challenges experienced by Indonesian EFL learners. The study further offers pedagogical implications for EFL teachers to provide more explicit instruction and targeted feedback on problematic spelling patterns, particularly silent letters and vowel combinations, to improve students’ writing accuracy.